Implementation of the Meningitis Vaccine Project in Africa: lessons for vaccine implementation programs - Obidimma Ezezika; Meron Mengistu; Thomas Lear (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background The Meningitis Vaccine Project (MVP) was an international partnership that began in 2010 and focused on the development, testing, licensure, and widespread introduction of a conjugate vaccine with the promise of protecting millions of lives from group A meningococcal meningitis. To bridge gaps upstream of vaccine administration and in understanding the project's planning, delivery and outcomes, the primary objective of this study was to delineate the barriers to and facilitators of sustainable implementation in an upstream context of the delivery of the MenAfriVac vaccine and to draw critical lessons for other vaccination programs. # Methods We conducted a qualitative study with key project partners and leaders who worked on the MVP project. The interviewees were initially identified through a literature review and a search of publications and evaluations of the project. Eighteen key stakeholders were interviewed. The interviewees included individuals in the roles of implementation oversight, champion, partner, funder, and frontline implementer. The Consolidated Framework for Implementation Research (CFIR) informed the identification of a priori codes for the directed content analysis. # Results There were multiple barriers and facilitators to implementing the vaccine under all five domains of the CFIR framework, including *intervention characteristics*, *outer setting*, *inner setting*, *characteristics of individuals*, and *process*. The most common domains mentioned by stakeholders that facilitated the success of the MVP were *inner setting* and *process*; specifically, three constructs were most representative-*Tension for Change, Formally Appointed Implementation Leaders, and External Change Agents*. # Conclusions The tension for change-that is, the degree to which stakeholders perceive the current situation as intolerable or needing change- advocated by African leaders served as a crucial foundation for solid leadership for the MPV. The leadership came in the form of the project director and other formally appointed leaders, who could plan, engage and execute the project's goals effectively. This leadership translated into consistent messaging, information sharing, and multiple levels of engagement with external change agents (including technical experts), which promoted a shared sense of readiness contributing to significant change investments in implementing MVP.